2020
DOI: 10.1108/jea-04-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Positive leadership: animating purpose, presence, passion and play for flourishing in schools

Abstract: PurposeThe purpose of this multiyear research study is to examine leadership in K-12 schools using a positive organizational perspective to understand how to foster, support and encourage flourishing in schools. In this article, the authors describe the lived experiences of a small group of principals and vice-principals in K-12 schools describing how they have experienced flourishing in their work.Design/methodology/approachThe research was carried out using a qualitative, phenomenological approach to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Attwood et al, 2020; Dodge et al, 2012). For example, a recent qualitative study carried out in Canada concluded that educational leaders’ well-being ‘was strongly related to the notion of balance in their work and life, which helped them address potential stress and ill-being’ (Cherkowski et al, 2020: 1). This suggests that, although educational practice varies by country, the well-being experiences of those leading the sector may share similar qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Attwood et al, 2020; Dodge et al, 2012). For example, a recent qualitative study carried out in Canada concluded that educational leaders’ well-being ‘was strongly related to the notion of balance in their work and life, which helped them address potential stress and ill-being’ (Cherkowski et al, 2020: 1). This suggests that, although educational practice varies by country, the well-being experiences of those leading the sector may share similar qualities.…”
Section: Discussionmentioning
confidence: 99%
“…In this example and in other organizations that possess cultures of excellence, the importance of positive leadership cannot be overstated. Positive leadership is characterized by instilling pride, purpose and a common set of values within followers (Cherkowski et al , 2020). In doing so, these leaders can develop organizations that are likely to be more effective and sustainable in the long run, which, of course, is a goal of cultures of excellence (Cameron et al , 2017).…”
Section: Cultures Of Excellencementioning
confidence: 99%
“…Presence varies according to one's personal history, beliefs, and experiences. In addition, presence represents more than just being visible; it also means being approachable, available to access the organization's status, and responsive to any issues 10 . Thus, presence may be what is needed to drive change in organizations and broader society 11 …”
Section: Introductionmentioning
confidence: 99%